Desenvolvimento de protótipo de pinça endoscopica para auxiliar a ressecção de lesão do tubo digestivo - Silva, Marcelo de Souza (2020)
Introduction: Gastrointestinal tumors are the second leading cause of cancer death worldwide, with about 990,000 new cases per year and 738,000 deaths. According to the National Cancer Institute (INCA), the incidence of tumors of the digestive tract was approximately 57,670 cases in 2018, 21,290 of which were gastric cancer. In 2017, there were 14,314 cases of gastric cancer. Adenocarcinoma is the histological type responsible for 95% of gastrointestinal cancer cases. Treatment will depend on the degree of spread. This pathology is studied by therapeutic endoscopy, which with its innovations enables early and efficient diagnosis and treatment. The treatment consists of dissecting the tumor under it, dissecting the submucosa, removing the first layer of the digestive tract, however this procedure can have complications such as bleeding and perforation, due to the difficulty in visualizing the vessels and the depth of the lesion during the dissection. Objective: Study the devices that assist in the endoscopic resection of the stomach and develop a prototype with this function. Methods: The first article reviews the past 20 years about endoscopic gastric tumor resection devices developed with the function of gastric resections. The second article corresponds to the process of developing a prototype seeking to improve the functions of the prototypes developed today. Results and discussion :The first proved to be of an inadequate size for the delicacy that this type of resection required, errors that were corrected in the second prototype, but other specific situations specific to the development of the medical clamp prototype appeared as the lack of adequate steel cables, making the movements of the robotic prototype. A third prototype was designed that is believed to correct all the flaws that were identified in the previous two prototypes, however due to many difficulties from projects to raw materials it was not prototyped, however it is believed that this prototype will be the solution for improve the resection of gastric tumors. Conclusion: After two prototypes with countless difficulties, we believe that we were able to design the third with the solution, but it was not possible to prototype it.